Opportunités et limites de l'agriculture de conservation en Méditerranée. Les enseignements du projet KASSA - Lahmar R. (Troisièmes rencontres méditerranéennes du semis direct, 2006)
Conservation agriculture is seen as a viable alternative in the Mediterranean context where it could constitute a response to the challenges of scarcity and degradation of the natural resources and to the instability of rainfed productions. The results of the KASSA project show that conservation agriculture is not equally suitable for all agro-ecosystems. The development and the sustainability of conservation agriculture systems are highly site specific. The shift from conventional agriculture to conservation agriculture is not a simple technical process. The involvement of the relevant stakeholders and their ability to generate and to share the knowledge necessary to develop, to adapt, to correct and to improve the systems are fundamental, particularly during the transition period where a continual adjustment of the systems is required. Furthermore, the functioning of the conservation agriculture systems and their long-term impacts are not known; they deserve more investigations in the future.
3. Mediterranean Meeting on no Tillage, 2006/03/23-25, Zaragoza (Spain)